2016
DOI: 10.1152/jn.00352.2016
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of spreading depolarization in vertebrate and insect central nervous systems

Abstract: Spreading depolarization (SD) is generated in the central nervous systems of both vertebrates and invertebrates. SD manifests as a propagating wave of electrical depression caused by a massive redistribution of ions. Mammalian SD underlies a continuum of human pathologies from migraine to stroke damage, whereas insect SD is associated with environmental stress-induced neural shutdown. The general cellular mechanisms underlying SD seem to be evolutionarily conserved throughout the animal kingdom. In particular,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 134 publications
6
44
0
Order By: Relevance
“…70,71 Indeed, multiple studies have shown beneficial properties of SD, including preconditioning, upregulation of growth factors, and neurogenesisis. [72][73][74][75][76][77] In addition, previous studies in insects [78][79][80][81] and rodents 72,73,82,83 suggest that SD may play a neuroprotective role during ischemia. 1,84 It is possible that this protection is enabled by a "neuronal silencing" mechanism associated with SD 85 wherein metabolism is quickly shut down, possibly to conserve residual energy and minimize production of reactive oxygen species, potentially leading to an improved survival and outcome in reversible processes.…”
Section: Discussionmentioning
confidence: 99%
“…70,71 Indeed, multiple studies have shown beneficial properties of SD, including preconditioning, upregulation of growth factors, and neurogenesisis. [72][73][74][75][76][77] In addition, previous studies in insects [78][79][80][81] and rodents 72,73,82,83 suggest that SD may play a neuroprotective role during ischemia. 1,84 It is possible that this protection is enabled by a "neuronal silencing" mechanism associated with SD 85 wherein metabolism is quickly shut down, possibly to conserve residual energy and minimize production of reactive oxygen species, potentially leading to an improved survival and outcome in reversible processes.…”
Section: Discussionmentioning
confidence: 99%
“…The weight of evidence, described in an accompanying review, 6 supports a conclusion that the neural mechanisms underlying SD in flies and mammals have a common molecular basis as a result of evolutionary conservation. For example, ouabain also induces SD in the mammalian brain.…”
mentioning
confidence: 83%
“…Clearly, this is would not 494 apply to most biological scenarios, which means that the results obtained with the 3-D implementation 495 are generally more reliable. In contrast to the 1-D model, the 3-D model predicts how ion concentrations 496 vary in the direction laterally from the neuronal sources, and can therefore be applied to new biological 497 problems such as spreading depression, which is associated with massive redistribution of ions that 498 spreads laterally in the cortex [3,7,54]. 499 The diffusion potentials addressed by the KNP-scheme are those that arise due to ECS concentration 500 gradients on relatively large spatial scales.…”
Section: Previous Models Of Ecs Electrodiffusion 483mentioning
confidence: 99%